Тактики емоційної аргументації в комунікативній поведінці ініціатора примирення - Передон, Наталія Олександрівна; Peredon, Nataliia O. (Запорізький національний університет, 2017)
Стаття присвячена аналізу тактико-стратегічного аспекту комунікативної поведінки ініціатора примирення в ситуації гармонізації міжособистісної інтеракції з комунікантом-об’єктом примирення. Виокремлено та проаналізовано особливості застосування тактик переконування, спрямованих на емоційну сферу сприйняття та осмислення інформації. Встановлено, що з метою відновлення комунікативного балансу з об’єктом примирення ініціатор примирення послуговується тактиками емоційної аргументації, до яких належать тактика демонстрації власного емоційного стану, тактика апеляції до попереднього позитивного досвіду спілкування, тактика самоосуду, тактика надання позитивної оцінки якостям та діяльності об’єкта примирення, тактика жарту і тактика посилання на авторитетні джерела. The article highlights the nature and peculiarities of the emotional argumentation tactics used by the party who is seeking to be the initiator of restored harmonious relations with the interlocutor who is the object of the initiative for reconciliation. The author comes to the conclusion that within the process of conflict resolution emotional argumentation is an effective means of influence as it helps persuade the object of reconciliation to change his / her negative attitude towards the initiator of reconciliation and interact harmoniously. It has been determined that the tactics of emotional argumentation are represented in the speech of the interlocutor who is seeking reconciliation by: 1) the tactics of demonstrating initiator’s emotional state. Using this tactics the initiator of reconciliation demonstrates his regret and shame aroused by his maleficent deed; 2) the tactics of appeal to the previous experience of harmonious interaction, the aim of which is to de-escalate conflict by referring to the feelings of love, affection and mutual understanding the interlocutors had before the conflict; 3) the tactics of self-condemnation which expresses the initiator’s critical attitude to his mental abilities and maleficent deed; 4) the tactics of appreciating the interlocutor’s qualities or behaviour, which helps show initiator’s positive attitude to the object of reconciliation; 5) the tactics of joke which lessens psychological distance between the initiator and the object of reconciliation; 6) the tactics of referring to authoritative sources. This tactics contributes to the conflict resolution by making the request for forgiveness more meaningful and significant.
Emotional Argumentation Tactics of Communicative Behaviour of the Initiator of Reconciliation
Keywords: тактики емоційної аргументації; ініціатор примирення; об’єкт примирення; emotional argumentation tactics; initiator of reconciliation; object of reconciliation